Asymmetric organocatalytic Michael addition of cyclopentane-1,2-dione to alkylidene oxindole - Silm, Estelle; Järving, Ivar; Kanger, Tõnis (Beilstein Journal of Organic Chemistry, 2022)
An asymmetric Michael reaction between cyclopentane-1,2-dione and alkylidene oxindole was studied in the presence of a multifunctional squaramide catalyst. Michael adducts were obtained in high enantioselectivities and in moderate diastereoselectivities.
Keywords: cyclopentane-1,2-dione; enantioselective catalysis; Michael addition; organocatalysis; squaramide